Peranan investasi asing langsung terhadap pertumbuhan ekonomi di negara-negara Asia Timur - Suryawati Suryawati (Economic Journal of Emerging Markets, 2000)
In many developing countries, Foreign Direct Investment (FDI) is expected to accelerate economic  development. For that reason, both host country and home country try to simulate the flow of FDI. The purpose of this article is to examine whether FDI affects to economic growth in east Asian or not.